Targeting CD155 by rediocide-A overcomes tumour immuno-resistance to natural killer cells - Wanyi Ng; Chenyuan Gong; Xuewei Yan; Guifan Si; Chen Fang; Lixin Wang; Xiaowen Zhu; Zihang Xu; Chao Yao; Shiguo Zhu (Taylor & Francis Group, 2021)
Context Therapeutic benefits of immunotherapy are restricted by cancer immune-resistance mechanisms. Rediocide-A (Red-A), a natural product extracted from Traditional Chinese Medicine, is a promising agent to battle against cancer which acts as an immune checkpoint inhibitor. Objective To investigate the effect of Red-A on NK-cell tumouricidal activity. Materials and methods NK cells were co-cultured with A549 or H1299 cells and treated with 10 or 100 nM Red-A for 24 h. Cells treated with 0.1% dimethyl sulphoxide (DMSO) was employed as vehicle control. NK cell-mediated cytotoxicity was detected by biophotonic cytotoxicity and impedance assay. Degranulation, granzyme B, NK cell-tumour cell conjugates and ligands profiling were detected by flow cytometry. Interferon-γ (IFN- γ) production was assessed by enzyme-linked immunosorbent assay (ELISA). Results Red-A increased NK cell-mediated lysis of A549 cells by 3.58-fold (21.86% vs. 78.27%) and H1299 cells by 1.26-fold (59.18% vs. 74.78%), compared to vehicle control. Granzyme B level was increased by 48.01% (A549 cells) and 53.26% (H1299 cells) after 100 nM Red-A treatment. INF-γ level was increased by 3.23-fold (A549 cells) and 6.77-fold (H1299 cells) after 100 nM Red-A treatment. Red-A treatment down-regulated the expression level of CD155 by 14.41% and 11.66% in A549 cells and H1299 cells, respectively, leading to the blockade of tumour immuno-resistance to NK cells. Conclusions Red-A overcomes immuno-resistance of NSCLCs to NK cells by down-regulating CD155 expression, which shows the possibility of developing checkpoint inhibitors targeting TIGIT/CD155 signalling to overcome immuno-resistance of cancer cells.